THE USE OF LANGUAGE IN SERVICE TO RESTAURANT GUESTS AT STAR HOTELS IN SAMOSIR REGENCY - Kamal, Mustafa (Akademi Pariwisata Darma Agung, 2022)
Service at the restaurant and bar in the hotel must be supported by staff who work well and politely. The staff in charge of serving food and drinks are known as waiters. Waiters must always understand the needs of guests and be able to serve guests well so that guests will feel satisfied, in this study located in restaurants in five-star hotels in Samosir Regency there are still many waiters from restaurants in five-star hotels constrained by the use of language, this obstacle due to one of the factors that made the guests feel uncomfortable because of the intonation conveyed by the waiter. This research is a descriptive qualitative research, namely the data collected in the form of words, pictures, not numbers. The purpose of descriptive research is to make a systematic, factual, and accurate description of the facts and characteristics of a particular population or area. it can be concluded that through the distribution of questionnaires, direct dialogue, and on-site observations, in several hotels, most of the waiters, both male and female, in using language such as greeting guests have not been carried out. They don't understand intangible services, or services that can't be felt physically directly by the waiter, are really no less important.